From Celebration to Continuous Improvement: A Mixed-Methods Strategic Event Management Framework - Mary Rose Montano; Ronald A Gonzales; Anna Rhea C Opeña; Aveto M Dasal Jr; Jeanne Mae L Ilao; Armando A Salenga Jr; Francis Eduard T Malitig; Lyka B Rodelas; Michael S Navarro; Meljhon G Mosca (Research Synergy Foundation, 2026)
School events play a vital role in strengthening institutional identity, stakeholder engagement, and the overall educational experience. However, many higher education institutions lack systematic, evidence-based approaches for evaluating these events and translating feedback into sustained improvement. This study evaluates a school graduation ceremony at the City College of Calamba to inform strategic and data-driven institutional event management practices. Using a convergent parallel mixed-methods evaluative approach, the study collected data from 274 stakeholders through a structured survey and open-ended responses to assess satisfaction across key dimensions of event planning and execution. Overall satisfaction levels were high, with mean scores ranging from 3.44 to 3.64 on a four-point Likert scale, indicating generally positive stakeholder perceptions. Technical and production quality received the highest rating (M = 3.64), while registration and rehearsal processes received the lowest (M = 3.44), highlighting specific areas for managerial improvement. No statistically significant differences in satisfaction were found across age, role, or department (p > 0.05), suggesting consistent event experiences across stakeholder groups. Based on these findings, the study proposes a Strategic Event Management Framework and corresponding Action Plan that translates evaluation results into concrete institutional management strategies. By reframing school events from isolated celebrations into strategically managed organizational activities, the framework supports continuous improvement, quality assurance, and institutional accountability. The study contributes to educational and institutional management literature by demonstrating how quantitative satisfaction indicators and qualitative feedback can be integrated to guide evidence-based decision-making in higher education event management.